2006
DOI: 10.1038/sj.ijo.0803471
|View full text |Cite
|
Sign up to set email alerts
|

Differential association of adiponectin with cardiovascular risk markers in men and women? The KORA survey 2000

Abstract: Background: In men, high adiponectin concentrations were related to a lower risk of myocardial infarction, whereas no association with cardiovascular events was found in women. Objective: To investigate sex differences in the associations of adiponectin with cardiovascular risk factors. Design: Cross-sectional population-based KORA Survey 2000 in Southern Germany using the same study methods for cardiovascular risk factors as the former WHO MONICA project. Participants: A total of 697 men and 657 women, aged 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 42 publications
4
27
2
Order By: Relevance
“…Previous studies (21,22,23,24) have convincingly shown that males have significantly lower levels of adiponectin than females. Data are scant as to whether this gender dimorphism results in any consequences in cardiometabolic conditions in females vs males.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (21,22,23,24) have convincingly shown that males have significantly lower levels of adiponectin than females. Data are scant as to whether this gender dimorphism results in any consequences in cardiometabolic conditions in females vs males.…”
Section: Introductionmentioning
confidence: 99%
“…The Dutch Hoorn Study demonstrated that the relationship between high total adiponectin level and lower risk of impaired glucose metabolism and type 2 diabetes was stronger among women than men in a group of 50-to 70-year-old subjects (11). However, no gender difference was revealed in the association of total adiponectin with cardiovascular risk factors in German subjects aged 55-74 years (KORA survey 2000) (24). Thus, data on gender-specific associations between adiponectin (especially HMW adiponectin) levels and cardiometabolic risk factors are rather limited so far.…”
Section: Introductionmentioning
confidence: 99%
“…Total cholesterol was measured by enzymatic methods (cholesterol oxidase-p-aminophenazone; Roche Diagnostics), HDL cholesterol was measured after precipitation with phosphotungstic acid/Mg 21 (Roche Diagnostics), and LDL cholesterol was measured after precipitation with dextran sulfate (Quantolip LDL; Immuno AG). Details on further laboratory measurements of the KORA S4 study are described elsewhere (30).…”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…Fasting insulin was determined by ELISA (Invitrogen). The IR score (HOMA-IR) was calculated (fasting plasma glucose (mmol/l)!fasting serum insulin (mU/l)/22.5) (19).…”
Section: Laboratory Measurementsmentioning
confidence: 99%